PENGELOLAAN OBJEK WISATA PERTANIAN AGROWISATA KAMPOENG KOPI BANARAN, PT. PERKEBUNAN NUSANTARA IX - Dradjat, Hasdevi Agrippina; Mugnisjah, Wahju Qamara (Jurnal Lanskap Indonesia, 2016)
People want an experience that’s completely different from their daily lives which can be done by enjoying tourism area, especially agrotourism area (Utama, 2011). Kampoeng Kopi Banaran (Kakoba) is an agrotourism of coffee, rubber and cocoa which main priority is to utilize its agriculural land as a tourism area. Kakoba has some geographically potencies, such as located in a strategic area among the triangle of Joglosemar (Jogjakarta, Solo and Semarang), good accesibility and has a coffee plantation as a visual landscape. Main goals of this study are to understand the users’ expectation, to make the recommendation of landscape management plan and to make the recommendation to reduce the gap between ideal and actual conditions. Several steps are used for this study such as observation, interviews, collecting literature study, and reporting the study in a final log book.. The methods used are both qualitative and quantitative methods. The results of this study are the understanding of the user’s expectation, a recommendation for Kakoba’s management plan, and recommendation to reduce the gap between ideal and actual conditions for agritourism management.